THE EFFECT OF COFFEE BREWING METHODS ON TOOTH DISCOLORATION - Rizki Nurida Rahmawati; Nadia Hardini; Lusiana Batubara (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: The color of teeth in each individual varies greatly in which it is influenced by the color of dentin and enamel. The most frequent tooth discoloration that happened is caused by extrinsic stains like coffee. Coffee consumption habits are increasing along with the level of creativity in serving coffee. Nowadays, coffee with conventional methods like black/Turkish coffee and manual brewing methods such as drip brewing and espresso become popular coffee that are fancied by Indonesian people. Exposure to chromogenic substances and the acidic nature of coffee can cause the formation of pores in enamel and facilitate the deposition of dyes, which cause the color changes. Aim: The aim of this research was to analyze the effect of brewing methods on tooth discoloration. Method: This research was a true experimental study with a pre-post test control group design. Twenty eight post-extracted first premolar teeth samples divided into 4 groups for drip, espresso, black coffee and control by implementing random allocation. All samples were immersed in each coffee brewing group for 3 hours, 6 hours, and 9 hours. The teeth color was measured using a Chromameter based on the CIE L*a*b system. Statistical tests used Kruskal Wallis and Mann-Whitney test. Result: The Kruskal Wallis test showed differences in the color change ∆a * between the four groups (p < 0.05). Mann-Whitney test indicated a significant difference between the treatment group (drip, espresso, and black coffee group) and the control group (p < 0.05). Conclusion: Drip coffee, espresso and black coffee brewing methods can affect tooth discoloration, especially affects the red discoloration. But there is no difference in the effect of the drip, espresso, and black coffee brewing methods on tooth discoloration.